An Experimental Study on the Non-Safety Pin Fire Extinguisher for the Elderly - Sang-Sig Kim; Ha-Sung Kong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, an experiment was conducted to see how the ability of the elderly to use fire extinguishers is affected by simplifying the steps of using a fire extinguisher so that the elderly in elderly care facilities can easily use a fire extinguisher for initial fire suppression. In order to prevent the user from panic in a fire situation and to find out the effects of the fire extinguishing operation stage, the operation of the existing fire extinguisher and the newly developed non-safety pin fire extinguisher were compared and analyzed. The results are summarized as follows. First, the number of steps for using a fire extinguisher was reduced to two steps with the non-safety pin fire extinguisher. It was confirmed that the time was reduced as the fire extinguishing agent was immediately discharged by lifting the fire hose without removing a safety pin. Second, it was confirmed that the new fire extinguisher can be easily used by the elderly and women, and the initial fire suppression time is reduced to less than 10 seconds for discharging the fire extinguishing agent. Third, the satisfaction with fire suppression by using the non-safety pin fire extinguisher was “high”, and its safety was confirmed. In addition, this work is intended to contribute to the development of firefighting technology by developing fire extinguishers with practical applicability.